Stock market reactions to layoff announcements in Finland 2010–2019 - Heinonen, Petteri (My University, 2022)
The main purpose of the study is to examine the Finnish stock market reactions to layoff announcements published by companies. Previous empirical research on the relationship between layoff announcements and the stock market has shown that the stock market generally reacts negatively to layoff announcements. Since prior empirical research has also shown that certain characteristics of layoffs may affect how the stock market reacts, the purpose is also to examine whether, among other things, the reason for the layoffs, the size of the layoffs, and the size of the company affect the stock market reaction. The full sample of the study consists of 384 layoff announcements published by 77 companies listed on the Nasdaq Helsinki in the years from 2010 to 2019. The layoff announcements are further divided into sub-samples to study the impact of the above-mentioned layoff characteristics on the reaction. The stock market reactions are measured by both abnormal returns and cumulative abnormal returns obtained using the event study methodology. The event window for which the abnormal returns are measured includes a total of 11 days, starting five days before the announcement date and ending five days after the announcement date. Moreover, the multivariate analysis is performed by testing the cumulative abnormal returns with the OLS regression model. The empirical results of the study indicate that the stock market reacts negatively to layoff announcements published by companies. On the date of the announcement, the average abnormal return for the full sample is -0,80 %. The results also indicate that the reason stated for the layoffs and the size of the company publishing the layoff announcement affect the reaction. Layoff announcements associated with declining demand or adverse market conditions cause a more negative stock market reaction than layoff announcements associated with improving efficiency. Layoff announcements of smaller companies, in turn, cause a more negative stock market reaction than layoff announcements of larger companies. The research findings may be valuable to investors in forming expectations concerning possible future layoff announcements and their impact on stock prices.

Tutkielman päätarkoituksena on tutkia Suomen osakemarkkinoiden reaktioita yritysten julkaisemiin lomautusilmoituksiin. Aiempi empiirinen tutkimus lomautusilmoitusten ja osakemarkkinoiden välisestä suhteesta on osoittanut, että osakemarkkinat reagoivat lomautusilmoituksiin pääsääntöisesti negatiivisesti. Koska aiempi empiirinen tutkimus on osoittanut myös, että tietyt lomautusten ominaisuudet saattavat vaikuttaa siihen, kuinka osakemarkkinat reagoivat, tarkoituksena on myös tutkia vaikuttavatko muun muassa lomautusten syy, lomautusten koko ja yrityksen koko osakemarkkinoiden reaktioon. Tutkimuksen koko otos koostuu 384 lomautusilmoituksesta, jotka 77 Helsingin pörssissä listattua yritystä ovat julkaisseet vuosina 2010–2019. Lomautusilmoitukset jaetaan alaotoksiin, jotta voidaan tutkia edellä mainittujen lomautusten ominaisuuksien vaikutuksia reaktioon. Osakemarkkinoiden reaktiot mitataan sekä epänormaaleilla tuotoilla että kumulatiivisilla epänormaaleilla tuotoilla, jotka saadaan käyttämällä tapahtumatutkimuksen metodologiaa. Tapahtumaikkuna, jolta epänormaalit tuotot mitataan, sisältää 11 päivää, alkaen viisi päivää ennen ilmoituspäivää ja päättyen viisi päivää ilmoituspäivän jälkeen. Lisäksi suoritetaan monimuuttuja-analyysi testaamalla kumulatiiviset epänormaalit tuotot OLS-regressiomallilla. Tutkimuksen empiiriset tulokset osoittavat, että osakemarkkinat reagoivat negatiivisesti yritysten julkaisemiin lomautusilmoituksiin. Koko otoksen keskimääräinen epänormaali tuotto ilmoituspäivänä on -0,80 %. Tulokset osoittavat myös, että lomautuksille ilmoitettu syy ja lomautusilmoituksen julkaisevan yrityksen koko vaikuttavat reaktioon. Lomautusilmoitukset, jotka liittyvät laskevaan kysyntään tai epäsuotuisiin markkinaolosuhteisiin, aiheuttavat negatiivisemman osakemarkkinareaktion kuin lomautusilmoitukset, jotka liittyvät tehokkuuden parantamiseen. Pienempien yritysten lomautusilmoitukset aiheuttavat puolestaan negatiivisemman osakemarkkinareaktion kuin suurempien yritysten lomautusilmoitukset. Tutkimuksen löydökset saattavat olla arvokkaita sijoittajille heidän muodostaessaan odotuksia mahdollisista tulevaisuuden lomautusilmoituksista ja niiden vaikutuksesta osakkeiden hintoihin.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance